Membangun Quality Function Deployment Untuk Meningkatkan Kepuasan Pasien Pada Rumah Sakit Di Kota Tegal - sujarwo, Makmur; Subekti, Subekti (Benefit: Jurnal Manajemen dan Bisnis, 2018)
Abstract: This study aims to find out how far the Quality Function Deployment (QFD) strategy is built in hospitals in the city of Tegal so that it can improve patient satisfaction. This study uses a questionnaire distribution method with a sample of 120 hospital patients in the city of Tegal as respondents. Respondents' answers to closed questions about the variables examined in this study were then analyzed using Multiple Regression Tests with IBM SPSS Statistics 22 analysis. The results of this study indicate variebel tangibles and emphaty which have a positive and significant effect on increasing patient satisfaction with successive regression values according to 0.340 and 0.559. For that reason, it has become a necessity for the hospital to further increase the tangible and empathetic of its patients in order to increase patient satisfaction. In the Quality Function Deployment (QFD) application, it shows that most of the requirements of patients (consumers) get value is very important and only a few who get important ratings, among others; rapid patient handling, the availability of sophisticated and modern hospital equipment technology; employees, nurses and doctors who are experts competent in their fields and friendly in serving patients, and others. Keywords : Quality Function Deployment, tangibles, reliability, responsiveness, assurance dan emphathy.. Abstraksi:Penelitian ini bertujuan untuk mengetahui sejauh mana strategi Quality Function Deployment (QFD) dibangun di rumah sakit di kota Tegal sehingga dapat meningkatkan kepuasan pasien. Penelitian ini menggunakan metode distribusi kuesioner dengan sampel 120 pasien rumah sakit di kota Tegal sebagai responden. Responden terhadap pertanyaan tertutup tentang variabel dianalisis menggunakan Uji Regresi Berganda dengan analisis IBM SPSS Statistics 22. Hasil penelitian ini menunjukkan variableness dan empati yang memiliki pengaruh positif dan signifikan terhadap peningkatan kepuasan pasien dengan nilai regresi berturut-turut sesuai 0,340 dan 0,559. Oleh karena itu, menjadi lebih penting bagi pasien untuk meningkatkan kepuasan pasien. Dalam aplikasi Quality Function Deployment (QFD), itu menunjukkan kondisi yang paling penting bagi pasien (konsumen), antara lain; penanganan pasien yang cepat, ketersediaan teknologi peralatan rumah sakit yang canggih dan modern; karyawan, perawat dan dokter yang ahli dalam bidangnya dan ramah dalam melayani pasien, dan lainnya.Kata kunci : Quality Function Deployment, tangibles, reliability, responsiveness, assurance dan emphathy.